Hydrophobic bioadhesive composites for human motion detection - Singh, Manisha (2022)
Conductive hydrogels are rapidly rising as sensing materials for bioelectronics applications, but lack mechanical and adhesion strength due to their excess water content. We propose a diazirine-grafted polycaprolactone adhesive (CaproGlu)/carbon nanotubes (CNTs) composite that can provide wet adhesion and strong mechanical properties at the tissue-machine interface. The introduced CNTs not only reinforced the CaproGlu, but also formed electrically conducting pathways. The CaproGlu composites exhibited conductivity of 0.1 S m-1 and a charge storage capacity of 5 μC cm-2. The resulting composites are biocompatible and can be used as strain sensors to detect mechanical deformations.